Diradicals Photogeneration from Chloroaryl‐Substituted Carboxylic Acids. Issue 26 (30th March 2022) - Di Terlizzi, Lorenzo; Protti, Stefano; Ravelli, Davide; Fagnoni, Maurizio
Abstract: With the aim of generating new, thermally inaccessible diradicals, potentially able to induce a double‐strand DNA cleavage, the photochemistry of a set of chloroaryl‐substituted carboxylic acids in polar media was investigated. The photoheterolytic cleavage of the Ar−Cl bond occurred in each case to form the corresponding triplet phenyl cations. Under basic conditions, the photorelease of the chloride anion was accompanied by an intramolecular electron‐transfer from the carboxylate group to the aromatic radical cationic site to give a diradical species. This latter intermediate could then undergo CO2 loss in a structure‐dependent fashion, according to the stability of the resulting diradical, or abstract a hydrogen atom from the medium. In aqueous environment at physiological pH (pH=7.3), both a phenyl cation and a diradical chemistry was observed. The mechanistic scenario and the role of the various intermediates (aryl cations and diradicals) involved in the process was supported by computational analysis. Abstract : New classes of thermally inaccessible diradicals having aggressive or stabilized radical sites have been generated under mild conditions by an Intramolecular Electron Transfer (IET) process occurring in photogenerated triplet phenyl cations.